SISTEM INFORMASI GEOGRAFIS TEMPAT PEMAKAMAN UMUM (TPU) DI WILAYAH KOTA PALEMBANG - Mazalisa, Zanial ; Irwansyah, Irwansyah (Universitas Bina Darma, 2016)
In accordance with the belief of Muslims that man comes from the ground and had to go back to the ground. Public Cemetery so that the problem is much needed for the community. Currently, the condition of the burial place General there is minimal from the local city government supervision, as is evident by the many Public Cemetery were not cared for properly. Of the problems and the above conditions of researchers trying to solve the problem by making a Geographic Information System General Cemetery in the city of Palembang in order to provide good information to the public. Geographic Information System is a computer-based information system that combines elements of the map (geographical) and information about the map, which is designed to acquire, manage, manipulate, analyze, demonstrate, manage and investigate the problem Keywords: public cemetery, geographic information systems, android